Rotational atherectomy for chronically and totally occluded coronary lesions: A propensity score-matched outcomes study - Tsai, Tien-Chien; Lo, Wei-Jung; Chen, Wei-Jhong; Lai, Chih-Hung; Su, Chieh-Shou; Chang, Wei-Chun; Wang, Chi-Yen; Liu, Tsun-Jui; Liang, Kae-Woei; Lee, Wen-Lieng; Chen, Yu-Wei (Frontiers in Cardiovascular Medicine, 2022)
Background Despite advances being made in techniques and devices, certain chronic total occlusion (CTO) lesions remain uncrossable or undilatable. Rotational atherectomy (RA) is usually necessary for such lesions to achieve successful revascularization. Methods Information regarding consecutive patients who underwent coronary RA was retrieved from the catheterization laboratory database. Patients who underwent RA for CTO lesion refractory using other conventional devices were recruited, with propensity score-matched cases serving as controls. Results A total of 411 patients underwent coronary RA in the study period. Most patients had high-risk features (65.7% had acute coronary syndrome (ACS), 14.1% ischemic cardiomyopathy, and 5.1% cardiogenic shock), while only 20.2% of the patients had stable angina. Among them, 44 patients underwent RA for CTO lesions (CTO group), whereas the propensity score matched controls consist of 37 patients (non-CTO group). The baseline characteristics, high-risk features, coronary artery disease (CAD) vessel numbers, left ventricular function and biochemistry profiles of both groups were the same except for more patients with diabetes (67.6% vs. 45.5%, p = 0.046) in the non-CTO group and more 1.25 mm burr uses in the CTO group. There were no significant differences in acute procedural outcomes or incidence of acute contrast-induced nephropathy (CIN), and no patient demanded emergent CABG or died during the procedure. There was no significant difference in major adverse cardiovascular events (MACE), CV MACE or individual components between the two groups in the hospital, at 30, 90, and 180 days or at 1 year. Conclusion In comparison with the propensity risk factor scores-matched controls, there was no difference in procedural complications, acute CIN or clinical outcomes during various stages of RA for CTO lesions. RA for CTO patients was highly efficient and showed safety and outcome profiles similar to those for non-CTO lesions.